1999
DOI: 10.1177/1368430299024003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Differential Status of Group Members on Process and Outcome of Deliberation

Abstract: Decision making groups, including European juries, often contain factions differing in status. Mock juries composed of trained and layperson status factions decided guilt and punishment for realistic cases of university code violations. Cases presented predominantly intellective or judgmental issues, and juries had to justify verdicts according to facts alone, or facts and values. Compared to laypersons, trained factions influenced group decisions more, but only in judgmental cases, or when having to include v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…This result corroborates the findings reported by Merle and Vitu (1967), who suggested that in the French system magistrates ''stabilize'' (Merle andVitu, 1967, p. 1036) the jury, meaning most likely that they influence them toward increasing the rates of conviction. These results may also be explained by the fact that generally, in groups, the sources that have the strongest influence are those whose status is more directly related to the task (Kaplan & Martin, 1999). Furthermore, Palmer observed that mixed juries changed their judgment more often and in opposite directions during the deliberation process compared with panels of naïve jurors.…”
Section: The Role Of Legal Knowledge In Decision-making Juriesmentioning
confidence: 85%
“…This result corroborates the findings reported by Merle and Vitu (1967), who suggested that in the French system magistrates ''stabilize'' (Merle andVitu, 1967, p. 1036) the jury, meaning most likely that they influence them toward increasing the rates of conviction. These results may also be explained by the fact that generally, in groups, the sources that have the strongest influence are those whose status is more directly related to the task (Kaplan & Martin, 1999). Furthermore, Palmer observed that mixed juries changed their judgment more often and in opposite directions during the deliberation process compared with panels of naïve jurors.…”
Section: The Role Of Legal Knowledge In Decision-making Juriesmentioning
confidence: 85%
“…Haley (1978) point of imbalance, stating that the differences in status allow professional judges to 33 For more general information on the imbalances in status and power affect the dynamics of mixedtribunals -particularly those of Germany -see also Kaplan and Martin (1999). In the end, cultural issues cannot entirely be ignored.…”
Section: Issues With and Concerns About Lay Participation In Japanmentioning
confidence: 99%
“…Deutsch (1973) also acknowledged informational influence as a source of individual or minority power saying that a group member might be influenced to accept third party information as being representative of a specific situation or fact even if that is not the case because of the informational power the influencing party has over them or the group. Kaplan and Martin (1999) supported this recognising expert power as an influence of minority power, defining it as a special knowledge or expertise about an issue that may influence a decision.…”
Section: Compromise Collaboration and Cooperationmentioning
confidence: 99%
“…In fact, projects benefit greatly from good requirements management principles, open and trusting environment, with business, stakeholders and developers working together in a collaborative and cooperative fashion, all to enable the sharing of viewpoints, clarification of conflict and consensus negotiation. Not surprisingly, in any decision making group participants commonly form distinctive and dissenting factions, even in spite of their shared social status (Kaplan & Martin 1999). On the other hand, as collaboration requires shared perceptions of all parties involved, this is more likely to come from members of a shared social status (Spekman 1996).…”
Section: Compromise Collaboration and Cooperationmentioning
confidence: 99%
See 1 more Smart Citation